2011
DOI: 10.4103/0972-0707.82613
|View full text |Cite
|
Sign up to set email alerts
|

The effects of halogen and light-emitting diode light curing on the depth of cure and surface microhardness of composite resins

Abstract: Aim:Light-emitting diode light curing units (LED LCUs) have become more popular than halogen LCUs in routine dental restorative treatment. The aim of the study was to compare the effects of two conventional halogen (Hilux Plus and VIP) and two LED (Elipar FreeLight 2 and Smart Lite) light curing units on the depth of cure and the microhardness of various esthetic restorative materials.Materials and Methods:The curing depth and microhardness of a compomer (Dyract Extra), a resin-modified glass ionomer (Vitremer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 12 publications
0
20
1
2
Order By: Relevance
“…In general, when the thickness of dental structure was increased a decrease in the VHN mean values was observed [39,45,46]. Frequently, for the top surface, the VHN mean values were equivalent.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In general, when the thickness of dental structure was increased a decrease in the VHN mean values was observed [39,45,46]. Frequently, for the top surface, the VHN mean values were equivalent.…”
Section: Discussionmentioning
confidence: 90%
“…The purpose of micro indentation hardness testing is to obtain a numerical value that distinguishes between the relative ability of materials to resist controlled penetration by a specified type of indenter which is generally much harder than the material being tested [25,37]. In a way of determining degree of polymerization, several studies have compared hardness of dental composite resins [37,[39][40][41]. Now, clinicians face a dilemma when selecting a protocol for light-curing techniques of light-cured dental composite resins.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of depth of cure, LED has been reported to cure similar or to increase depths through the resin composites (Apicella et al, 2002;Simeone et al, 2005;Ruchi et al, 2010). Considering the surface micro-hardness, several studies (Yaman et al, 2011) reported that LED-curing results is better micro-hardness than QTH. These results are suggesting that the type of curing light source may affect the level of polymerization and cross linking of the resin through the composite leading to higher surface hardness and glass transition temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…The polymerization of light cured materials depends on their chemical composition, on the amount of filler particles, as well as on spectral output and irradiance of blue light emitted by light curing units (LCUs) [6][7][8]. Dentists may choose from different types of curing lights for the photo-polymerization of composites, such as conventional quartz tungsten-halogen (QTH/ HAL), light emitting diode (LED) curing units [9]. QTH/HAL is commonly preferred dental light curing unit [10].…”
Section: Introductionmentioning
confidence: 99%